Leadership in Staff Training in the Armed Forces of the Czech Republic - David ULLRICH; Jan ZEZULA; Vratislav POKORNÝ; Miroslav POLACH (Communications of International Proceedings, 2020)
The article describes the method of preparation and education of future military professionals in the field of direct leadership in the conditions of the University of Defence in Brno. The first part describes the process of preparation and education of students of the University of Defence in Brno in subjects related to direct leadership (applied behavioral science, leadership, military leadership and field preparation). The second part describes their interconnection, which is the result of a combination of identified requirements and competencies for military leadership.
Keywords: communication; Czech Armed Forces; leadership; military leader; military professional ethics; military psychology; University of Defence.